2018
DOI: 10.1155/2018/5943914
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the High-Performance Liquid Chromatography Fingerprints and Quantitative Analysis of Multicomponents by Single Marker of Products of Fermented Cordyceps sinensis

Abstract: Fermented Cordyceps sinensis, the succedaneum of Cordyceps sinensis which is extracted and separated from Cordyceps sinensis by artificial fermentation, is commonly used in eastern Asia in clinical treatments due to its health benefit. In this paper, a new strategy for differentiating and comprehensively evaluating the quality of products of fermented Cordyceps sinensis has been established, based on high-performance liquid chromatography (HPLC) fingerprint analysis combined with similar analysis (SA), hierarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…However, the current standard quality protocols do not completely reflect the quality of Jinshuibao capsules and Jinshuibao tablets. Therefore, the development of a method to control the quality of Jinshuibao products more systematically and effectively is an urgent issue (Chen, Wu, & Guan, 2018). With the continuous improvement of TCM quality requirements, fingerprint has become more and more important for TCM quality control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the current standard quality protocols do not completely reflect the quality of Jinshuibao capsules and Jinshuibao tablets. Therefore, the development of a method to control the quality of Jinshuibao products more systematically and effectively is an urgent issue (Chen, Wu, & Guan, 2018). With the continuous improvement of TCM quality requirements, fingerprint has become more and more important for TCM quality control.…”
Section: Introductionmentioning
confidence: 99%
“…These multivariate statistical methods comprehensively revealed the relationship of chemical components of medicinal materials and their geographical origins and authenticity (Chen, Zhu, & Tang, 2017; Yi et al., 2013), and also achieved the better quality control on medicinal materials and their products (Esteki et al., 2019). However, the fingerprint only reflects the general characteristics of the contents of TCM and serves only as an indicator of their quality, so multicomponent quantitative analysis was developed for application in comprehensive quality control (Chen et al., 2018). The quantitative analysis of multicomponents by single marker (QAMS) method determines the content of multicomponent substances by establishing a relative correction factors (RCFs) between a sample and the content of a reference substance (Jiang, Chen, & Wang, 2016; Stavrianidi, Stekolshchikova, & Porotova, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the special distribution, high price, and excessive exploitation, the usage of C. sinensis has been limited during the past decades (Wang et al., 2014). Therefore, much effort has be focused on the cultivation technology of C. sinensis and the discovery of the alternative substitutes (Chen, Wu, Guan, Jin, & Yang, 2018; Wang et al., 2015; Yao et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Fermented Cordyceps powder is made by liquid deep fermentation and processing. Studies have confirmed that the chemical constituents of fermented Cordyceps powder products are similar to those of Cordyceps sinensis , mainly including nucleosides, sterols, polysaccharides, and amino acids, which have anti-inflammatory, antioxidant, and immune regulation pharmacological effects and can be used as sustainable substitutes for Cordyceps sinensis [ 1 – 6 ]. At present, fermented Cordyceps powder preparation products are diverse on the market, including Jinshuibao Capsules, Jinshuibao Tablets, Bailing Capsules, Ningxinbao Capsules, Xinganbao Capsules, etc.…”
Section: Introductionmentioning
confidence: 99%